Fat Mass Follows a U-Shaped Distribution Based on Estradiol Levels in Postmenopausal Women - Colleluori, Georgia; Chen, Rui; Napoli, Nicola; Aguirre, Lina E.; Qualls, Clifford; Villareal, Dennis T.; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2018)
Objective Estradiol (E2) regulates adipose tissue resulting in increased fat mass (FM) with declining E2. However, increased visceral fat and hyperestrogenemia are features of obese individuals. It is possible that adipocytes in obese individuals are less sensitive to E2 resulting in higher FM. Our objective is to identify the range of serum E2 for which postmenopausal women have the lowest FM and best body composition. Methods Cross-sectional data from 252 community-dwelling postmenopausal women, 42–90 years old. Subjects were stratified into categories of E2 (pg/ml): (1) ≤10.5; (2) 10.6–13.9; (3) 14.0–17.4; and (4) ≥17.5. Body composition by dual-energy X-ray absorptiometry. Serum E2 by radioimmunoassay. Between-group comparisons by analysis of covariance. Results E2 linearly increased with increasing body weight and body mass index (r = 0.15 and p = 0.01 for both), but not with total FM (kg) or % FM (r = 0.07, p = 0.34 and r = −0.04, p = 0.56, respectively). However, total FM (kg) followed a U-shaped distribution and was significantly lower in group 3 (27.6 ± 10.6), compared with groups 1: (34.6 ± 12.5), 2: (34.0 ± 12.4), and 4: (37.0 ± 10.6), p = 0.005. % FM was also lowest in group 3. While fat-free mass (FFM, kg) increased with increasing E2 (p < 0.001), % FFM was highest in group 3. Conclusion In our population of postmenopausal women, FM followed a U-shaped distribution according to E2 levels. E2 between 14.0 and 17.4 pg/ml is associated with the best body composition, i.e., lowest total and % FM and highest % FFM. Given the role of E2 in regulating body fat, high FM at the high end of the E2 spectrum may suggest reduced E2 sensitivity in adipocytes among obese postmenopausal women. Clinical Trials ClinicalTrials.gov identifier: NCT00146107.